Blob properties in full-turbulence simulations of the TCV scrape-off layer. (21st March 2017) - Nespoli, F; Furno, I; Labit, B; Ricci, P; Avino, F; Halpern, F D; Musil, F; Riva, F
Abstract: To investigate blob properties in the tokamak scrape-off layer (SOL), we perform dedicated numerical nonlinear simulations of plasma turbulence in the SOL of a TCV discharge using the Global Braginskii Solver code. A blob detection technique is used for the first time in a three-dimensional (3D) full-turbulence simulation to track the motion of the filaments in the SOL. The specific size, density amplitude and radial velocity of the blobs are computed, with the typical values being 7.4 ρ s, 0.33 n e and 0.016 c s, respectively. The analysis of blob structure in the parallel direction shows that the blobs are partially detached from the limiter. The cross correlation analysis shows how the blobs are born all along the entire field line, not being generated primarily on the low field side SOL and expanding towards the limiter. The blob radial velocity agrees well with the inertial branch of the existing scaling law. The radial particle and heat fluxes given by blobs are shown to be responsible of up to 100% and 70% of the turbulent particle and heat flux in the far SOL, respectively. The results of a second simulation with a 40 times higher resistivity are also discussed.